From Aunt Chilada's to Cactus Willy's: Gender Naming in the Marketing of Food in Arizona - Alleen Pace Nilsen (Names, 1995)
Abstract Many food products and restaurant names, while apparently genderless, are found to be gender marked. In grocery stores, items divide almost equally between masculine and feminine. More restaurants are perceived masculine than feminine. Personal names on products and restaurants communicate a sense of trust, ethnicity, and formality.